Dampak Krisis Di Indonesia Yang Mengakibatkan Kerapuhan Fundamental - Firda Ananda Yulia Sari; Rizky Himawan Saputra; Muhammad Yasin (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The economic crisis that hit Indonesia has resulted in fundamental fragility in various aspects of state life. The impact of this crisis is not only limited to the economic sector, but also extends to the social, political and government sectors. This research analyzes how the crisis affects the economic structure, political stability and social welfare of society. Through a qualitative approach using case study methods, this research found that the fundamental fragility that occurred was caused by weak economic infrastructure, rampant corruption and ineffective government policies. In addition, this crisis exacerbates social inequality and results in increasing poverty and unemployment rates. This study recommends the need for structural reforms and more inclusive and transparent policies to mitigate the impact of the crisis and strengthen Indonesia's fundamental foundations.